Splanchnic Hypoperfusion and Enteral Feeding - Wina Sinaga; Luciana Budiati Sutanto; Ari Fahrial Syam (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2013)
Hypoperfusion or decrease in blood flow is may cause organ failure. When the body experiences hypoperfusion, body perfusion is prioritized to brain and heart, which may cause the hypoperfusion of splanchnic organ. Splanchnic hypoperfusion will cause ischemia of the mucosa, disturbance in the barrier, and increased splanchnic permeability, which in further level mayl cause bacterial and endotoxin translocation to systemic circulation.Enteral feeding in hypoperfusion is beneficial to prevent splanchnic hypoperfusion. However, method of enteral feeding needs to be considered, so that it does not cause harmful adverse effects. Early enteral feeding by slow continuous drip method can prevent splanchnic failure in critically ill patients with high risk of hypoperfusion. Keywords: splanchnic hypoperfusion, enteral feeding, continuous slow drip method